POSSIBILITIES OF BREAD ENRICHMENT WITH MINERALS BY USING SUGAR BEET MOLASSES - Vijolė Bradauskienė; Loreta Tamošaitienė; Vitalija Freitakaitė; Mihaela Adriana Tita (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Various scientific researches proved that the most important macro and microelements for human health are potassium, calcium, iron, magnesium. Sugar beet molasses (SBM), which is a concentrated liquid extract and a by-product of sugar refining, is full of mentioned macro and micronutrients. The aim of the research is to study the possibilities for the use of sugar beet molasses in the production of rye bread enriched with minerals. For the study, the sugar beet molasses from JSC Lietuvos cukrus Ltd was used. Five samples of rye bread (control, 8%, 10%, 12%, 14% addition of SBM to flour mass) were prepared and baked. To estimate the influence of sugar beet molasses on the quality and acceptability of the bread for consumers, the sensory evaluation of the bread samples was carried out; the moisture content, the acidity, the actual acidity, the specific volume of the bread were defined; the number of minerals in molasses was estimated by laboratory tests; and also the nutritional value of the bread was calculated. The study showed that when up to 10% molasses is added to the total flour mass in rye bread, the sensory parameters in comparison with the control product are superior: better aroma, the appearance of dark colour, soft texture and good taste. There was no significant impact on the specific volume and titratable acidity of the bread. The most acceptable for evaluators was the bread with 50 g molasses added to 1kg bread sample. The results showed that the mineral content (K, Fe, Ca) of the rye bread samples were significantly improved. The bread that contains molasses is a good source of iron (14.31-18.08% of DRIs).